Evaluation of Mineral-Based Zn-Doped Hydroxyapatite as a Photocatalyst for Methylene Blue Degradation - Nisrina, Aniqa; Karya, Teguh; Halim, Riyan; Murniati, Anceu; Hardian, Arie; Gustaman Syarif, Dani; Rostika Noviyanti, Atiek; Jasmansyah, Jasmansyah; Reza, Muhammad (The Journal of Pure and Applied Chemistry Research, 2024)
Methylene blue is a synthetic dye known to be harmful to aquatic environments. Therefore, efforts are needed to minimize methylene blue waste. This study focuses on degrading methylene blue through photocatalysis, a method chosen for its affordability and ease of use. The photocatalyst used is hydroxyapatite (HAp) derived from limestone (CaCO3) doped with zinc ions (Zn2+). This combination enhances the efficiency of breaking down dye molecules in liquid waste. The photocatalytic performance was tested under three variations: solution concentration, contact time, and pH, using an 8-watt UV lamp for specified durations. Solution absorbance was measured using a Shimadzu 1800 UV-Vis spectrophotometer. Optimal conditions for methylene blue photodegradation by Zn-doped HAp were achieved at 67.2% efficiency for 5 ppm concentration, 16.125% for 120 minutes of irradiation, and 34.86% at pH 7. Additionally, the study included an analysis of adsorption isotherm models for concentration variation and kinetic adsorption analysis for time variation. The Langmuir and Temkin adsorption isotherm models were found to be most suitable with an R2Â = 1. The photodegradation kinetics model followed pseudo second-order kinetics with an R2Â = 0.990.